The Relationship Between Credentials and SOP Compliance with the Performance of Other Health Workers at Balaraja Regional Hospital - Sutanto; Djaali, Nur Asniati; Jumhati, Siti (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
According to data from the Balaraja Regional Hospital's quality subcommittee, there has been a decline in the performance of other healthcare workers, including miscommunication, lack of patient information, errors in medication inventory records, and inadequate staffing to handle certain medical devices or procedures. This can significantly impact the overall quality of healthcare services provided to patients. Aims To determine the relationship between credentials and compliance with SOP on the performance of other healthcare workers at Balaraja Regional Hospital. This type of research is an observational analytic with a cross-sectional approach. The sample of this study was 115 non-medical and non-nursing personnel at Balaraja Regional Hospital. The sampling technique used a stratified random sampling method. Data were analyzed bivariately using the chi-square test and multivariate analysis using multiple logistic regression. There is a significant relationship between credentials variables and the performance of other healthcare workers after being controlled by education with a p value of 0.004 (p < α 0.05) and there is a significant relationship between compliance with SO0P on the performance of other healthcare workers after being controlled by education with a p value of 0.020 (p < α 0.05). Based on the characteristics of the respondents, most were female, aged >35 years and had a Bachelor's degree. Most respondents performed well, and had competent credential assessments and complied with Standard Operating Procedures. There was a significant relationship between the credential variable and the performance of other health workers at Balaraja Regional Hospital after being controlled by education. It was also known that there was a significant relationship between the SOP compliance variable and the performance of other health workers at Balaraja Regional Hospital after being controlled by education. The most dominant variable related to the performance of other health workers at Balaraja Regional Hospital was credentials. Improve the credential system by adjusting the instrument and credential planning according to competency development, maintaining a credential sub-committee that assesses competency objectively by training credential assessors. Conduct regular socialization of SOP, provide clear, concise, and easy-to-understand SOP.